serologic markers of Epstein-Barr virus reactivation in the conditions of viral encephalitis in young patients - O. V. Goleva; E. A. Murina; Z. A. Osipova (Журнал инфектологии, 2015)
The reactivation of Epstein-Barr virus on the background of some basic disease revealed during the development of encephalitis of various etiology could act as a co-factor to trigger the process of demyelinazation of central nervous system tissues. Purpose: to clarify the role of persistent Epstein-Barr virus infection in children with the diagnosis of viral encephalitis. Materials and methods: there was performed the study of biological material (blood serum) of 29 children aged from 1 to 14 years old with the diagnosis of viral encephalitis during the period of 2012–2013. The algorithm of the study included serological methods on the basis of the enzymelinked immunosorbent assay manufactured by Joint-Stock Company «Vector-Best» (Novosibirsk) on the open-type apparatus «Lasurit» of «Dynex Technologies Inc.» company (USA) and blot-technologies with the use of Western-blotting manufactured by Euroimmun AG, Germany on the apparatus «AUTOBLOTT 3000» of «MedTec, Inc.» company (USA). Results: It was determined that during the testing of the late phase Epstein-Barr antibodies (IgG-NA and IgG-VCA) with the indicators of high avidity index, the blot-technology use also revealed IgG class antibodies to the early phase antigenes of this virus (EA-R, and EA-D), synthesized within the period of not longer than three weeks beginning from the disease onset. This allowed to assume the development of an active phase of chronic Epstein-Barr virus infection in the observed patients. The antibodies to an early antigen were noticed particularly often in the case of encephalitis caused by varicella zoster virus that composed 62,5% of total number of cases with the development of encephalitis of given etiology. Conclusion: in the case of associated infections by those viruses among which there are etiologically significant ones for encephalitis development, Epstein-Barr virus, the infection by which occurred earlier, can be activated and influence the development of the pathologies connected with demyelinazation of central nervous system tissue.